(untitled) (Research, Society and Development, 2021)
Cancer is the main public health problem in the world and is already among the four main causes of premature death. Cancer is the name given to diseases that present disorganized cell growth, from there to the invasion of tissues and organs. Worldwide, breast cancer is the most common among women. Whose treatment is performed through a surgical procedure that can be a conservative surgery, with removal only of the tumor; or mastectomy, with removal of the breast and breast reconstruction, in addition to supporting techniques, which include radiotherapy, chemotherapy and hormone therapy. The study has as general objective to understand the contributions of the Systematization of Nursing Care (SAE) in the health-disease process of women with mastectomies. It refers to an Integrative Literature Review study. Ten articles were selected, with a time frame between 2015 and 2020 on the presence of evidence aimed at the realization of the Nursing Care Systematization (SAE) in relation to the quality of life of women with mastectomies. It was concluded that the SAE, when correctly used, can be a methodological reference for the humanization of women’s health care, promoting effectiveness in care, support, bonding with the patient, increased confidence in nursing activities and reduction of health costs.